Differences in Misreporting of Sexual Behavior Over Time: Implications for HIV Trials. Issue 3 (March 2015) - Gallo, Maria F.; Warner, Lee; Hobbs, Marcia M.; Jamieson, Denise J.; Hylton-Kong, Tina; Steiner, Markus J.
Abstract : Abstract: We used data from a prospective study of 300 women attending a sexually transmitted infection clinic in Kingston, Jamaica, to compare participant self-report of recent semen exposure to actual semen exposure measured by prostate-specific antigen in vaginal swabs. Underreporting of semen exposure was significantly more frequent at follow-up than baseline, suggesting that the accuracy of reports of sexual behavior may vary over time. Abstract : Participant underreporting of exposure to semen increased over time. Misclassification of participant reports of sensitive behaviors cannot be assumed to occur at random.